Antígenos alimentarios más frecuentes e IgE en pacientes con urticaria en la ciudad de Loja en el periodo de marzo-agosto del 2014 - Álvarez Merchán, Marcia Stefania (2015)
Between 30 and 40% of the world population is affected by one or more allergic diseases. The allergy is considered an overreaction to contact with allergens. Are multiple diseases including allergies have asthma, allergic rhinitis, atopic dermatitis and urticaria among others. The urticaria are one of the most frequent reasons for consultation in medical practice, children and young adults are the most affected by urticaria foodborne with incidence of 25-33%. It is more common to find the main meter IgE allergic reaction. This research included 75 patients based on clinical history were diagnosed with urticaria, underwent Prick Test (Skin Test) with 7 antigens food type (orange, peanuts, eggs, milk, tomato, shrimp and strawberry ) and then proceeded to the determination of serum IgE. The results were: the food and causing sensitizing urticaria was orange, followed by shrimp and thirdly tomato and strawberry. IgE levels in patients of all ages showed higher values in relation to the normal range. By correlating the awareness of food antigens in relation to levels of IgE, it was observed that most of them had high levels of IgE. The shrimp feed was that induced the highest levels of IgE, in some cases it was observed immunoglobulin E levels that exceed 1000 IU / ml. Most patients diagnosed with urticaria were aged between 16 and 20 years. Keywords: food antigens, IgE, urticaria.